Gel integration for microfluidic applications. Issue 10 (18th April 2016) - Zhang, Xuanqi; Li, Lingjun; Luo, Chunxiong
Abstract : We systematically review the physical properties of hydrogels, general methods for gel–microfluidics integration and applications of this field. Abstract : Molecular diffusive membranes or materials are important for biological applications in microfluidic systems. Hydrogels are typical materials that offer several advantages, such as free diffusion for small molecules, biocompatibility with most cells, temperature sensitivity, relatively low cost, and ease of production. With the development of microfluidic applications, hydrogels can be integrated into microfluidic systems by soft lithography, flow–solid processes or UV cure methods. Due to their special properties, hydrogels are widely used as fluid control modules, biochemical reaction modules or biological application modules in different applications. Although hydrogels have been used in microfluidic systems for more than ten years, many hydrogels' properties and integrated techniques have not been carefully elaborated. Here, we systematically review the physical properties of hydrogels, general methods for gel–microfluidics integration and applications of this field. Advanced topics and the outlook of hydrogel fabrication and applications are also discussed. We hope this review can help researchers choose suitable methods for their applications using hydrogels.